2021
DOI: 10.3390/foods10040882
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Elimination in Emulsified Meat Products: Impact of Protein-Based Ingredients on Quality Characteristics

Abstract: The addition of phosphates to meat products improves the emulsifying and gelling properties of meat proteins, in turn enhancing overall product quality. The current market trend towards additive-free products and the health issues related to phosphate challenge the industry to develop phosphate-free meat products. The aim of this study was to evaluate the potential of seven protein-based ingredients (pea, blood plasma, gelatin, soy, whey, egg, and potato) to remediate quality losses of emulsified meat products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 64 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…The higher the TEF percentage, the lower the emulsion stability. The replacement of animal fat by GE (at any percentage) did not cause significant differences (p > 0.05) in emulsion stability, values ranging from 1.03 to 1.72 % (Figure 1) in all samples, which is according to normal values for these type of sausages [17]. Some authors have reported that the simple reduction of back fat in cooked sausages decreased their stability [13].…”
Section: Emulsion Stability Of Meat Battersmentioning
confidence: 56%
See 2 more Smart Citations
“…The higher the TEF percentage, the lower the emulsion stability. The replacement of animal fat by GE (at any percentage) did not cause significant differences (p > 0.05) in emulsion stability, values ranging from 1.03 to 1.72 % (Figure 1) in all samples, which is according to normal values for these type of sausages [17]. Some authors have reported that the simple reduction of back fat in cooked sausages decreased their stability [13].…”
Section: Emulsion Stability Of Meat Battersmentioning
confidence: 56%
“…sausages [17]. Some authors have reported that the simple reduction of back fat in cooked sausages decreased their stability [13].…”
Section: Emulsion Stability Of Meat Battersmentioning
confidence: 99%
See 1 more Smart Citation
“…In sodium-reduced chicken breast myofibrillar protein gel, high pressure processing and calcium have been used to increase the water holding capacity [ 74 ]. Moreover, in emulsified meat products such as sausages, phosphate elimination affected the gelling characteristics of the products, and egg or pea addition remediated the quality loss [ 75 ]. More importantly, two transglutaminase enzymes were used in the restructured beef steaks to create covalent linking between meat proteins and improve the quality [ 76 ].…”
Section: Proteins In Meatmentioning
confidence: 99%
“…Although not harmful for healthy people, EFSA found that the exposure was higher than the acceptable daily intake for some population groups [ 8 ]. Goemaere et al [ 10 ] studied the use of seven protein-based ingredients as phosphate replacers in emulsified meat products. The authors found that blood plasma and soy were superior in phosphate-free cooked sausages compared with sausages containing phosphates, in terms of texture, cooking yield, and stability.…”
mentioning
confidence: 99%